Performance Of Islamic Rural Banks Pre and During Pandemic By Maqashid Sharia Index - Rahmi Amalia; Asmaul Husna; Sarwo Edi (Universitas Islam Negeri Alauddin Makassar, 2022)
This study attempted to reveal the performance of the Islamic Rural Bank (BPRS) in North Sumatra during the pre and post-covid-19 pandemic. The method used in this study uses descriptive quantitative research with secondary data sources, namely the financial statements of BPRS in North Sumatra published on the site of Otoritas Jasa Keuangan (OJK) for 2019-2021. The data were selected by purposive sampling and obtained 7 BPRS according to the research criteria. This study used the Maqashid Syariah Index as a performance measurement method, based on the definition of Abu Zahrah maqasid shariah model. The findings in this study are, during 2019-2021, the average performance level of BPRS Gebu Prima in Medan city was the highest at 37.5%, and BPRS al-Washliyah was the lowest at 22.55%. The results showed some elements are negatively affected by the covid-19 pandemic, such as very low levels of profitability. This research contributed to providing information to BPRS stakeholders in North Sumatra to continuously improve performance in the Maqashid Sharia dimension.